Can baseline C-reactive protein level predict functional outcome in acute ischaemic stroke? A meta-analysis. (2nd October 2020) - Hu, Ziyi; Lai, Junyu; Chen, Lisha; Yi, Ying; Li, Renliang; Liao, Weimin
Abstract: Background: The association between elevated C-reactive protein (CRP) level and poor functional outcome is conflicting in acute ischaemic stroke (AIS) patients. This meta-analysis sought to investigate the value of elevated CRP level in predicting poor functional outcome in AIS patients. Material and methods: A systematically literature search was performed in PubMed and Embase databases up to 31 October 2019. Prospective and retrospective studies evaluating the association between elevated CRP level and poor functional outcome (defined by the modified Rankin scale ≥3) beyond 3 months after AIS were included. Results: Ten studies with a total of 8087 AIS patients were identified in this meta-analysis. When compared with reference low CRP level, the highest CRP level was associated with an increased risk of poor functional outcome (multivariate-adjusted hazard ratio (HR) 1.99; 95% confidence interval (CI) 1.63–2.44) in a random effect model. Sensitivity analysis further confirmed the significance of CRP elevation for predicting poor functional outcome after AIS. Conclusions: Elevated CRP level is significantly associated with poor functional outcome in patients with AIS. Baseline CRP level has potential to improve risk stratification of function outcome in AIS patients.